2019
DOI: 10.1002/ana.25379
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes Depending on Acute Blood Pressure After Cerebral Hemorrhage

Abstract: ObjectiveTo determine the association between clinical outcomes and acute systolic blood pressure (SBP) levels achieved after intracerebral hemorrhage (ICH).MethodsEligible patients who were randomized to the ATACH‐2 (Antihypertensive Treatment in Intracerebral Hemorrhage 2) trial (ClinicalTrials.gov: NCT01176565) were divided into 5 groups by 10‐mmHg strata of average hourly minimum SBP (<120, 120–130, 130–140, 140–150, and ≥ 150 mmHg) during 2 to 24 hours after randomization. Outcomes included: 90‐day mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…[101,102] combined the results of these (and other) trials, but these are of limited clinical relevance given the major differences between the INTERACT-2 and ATACH-2 trials. A subanalysis of ATACH-2 found that by lowering the blood pressure below 120-130mmHg the benefits of preventing haematoma expansion were offset by increased cardio-renal adverse events [103]. Large-scale individual patient data analyses of the INTERACT-2 and ATACH-2 trial data are awaited.…”
Section: Acute Blood Pressure Loweringmentioning
confidence: 99%
“…[101,102] combined the results of these (and other) trials, but these are of limited clinical relevance given the major differences between the INTERACT-2 and ATACH-2 trials. A subanalysis of ATACH-2 found that by lowering the blood pressure below 120-130mmHg the benefits of preventing haematoma expansion were offset by increased cardio-renal adverse events [103]. Large-scale individual patient data analyses of the INTERACT-2 and ATACH-2 trial data are awaited.…”
Section: Acute Blood Pressure Loweringmentioning
confidence: 99%
“…The vast majority of cerebral hemorrhage is manifested as small artery rupture caused by hypertension, which can cause extremely serious symptoms within a short period of time, and even affect patients' basic physiological activities such as breathing and heartbeat, resulting in death. It is a common acute cerebrovascular disease in middle-aged and elderly people, with a high fatality and disability rate [18]. The patient had no history of hypertension, sudden cerebral hemorrhage, and no vascular abnormalities such as aneurysms during the operation.…”
Section: Discussionmentioning
confidence: 99%
“…Rupture of a small artery caused by high blood pressure can lead to death shortly due to effects of bleeding on the body's main activities, such as breathing and heart pumping. Acute cerebrovascular diseases are one of the most common diseases in middle-aged and elderly people, and with its wide range of effects, it can lead to high mortality and disability [22]. Studies have also shown that in addition to a pandemic, the coronavirus will cause a widespread stroke epidemic [23].…”
Section: Discussionmentioning
confidence: 99%